Pandangan Masyarakat Islam Surabaya terhadap Kriminalisasi Nikah Sirri dalam Reformasi Hukum Keluarga di Indonesia - Masruhan, Masruhan (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2019)
The people who committed unregistered marriage as criminal and penalized by imprisonment has created some problems. Marriage in Islam is considered as worship so it is not supposed to be criminalized. On the other hand, most leaders and figures in Surabaya opprove to criminalize who committed sirri marriage and polygamy as criminal and punished by imprisonment has created as worship so it is not supposed to be criminalized. On the other hand, most leaders and figures in Surabaya approve to criminalize sirri marriage. Furthermore, a husband who refuses to take responsibility, someone who acts as a trustee but entitled to do it and divorce which was not conducted by the judicial court can also be considered as criminal acts.